2020
DOI: 10.5226/jabmech.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wavy Leading Edge on Pitching Rectangular Wing

Abstract: Experimental and numerical study on the effect of wavy leading edge (WLE) on pitching rectangle wings were conducted using NACA 0018 airfoil. The shape of WLE is sinusoidal function. URANS simulations were employed using SST k-ω turbulence model. The WLE wing has preferable forces at the poststall region compared to baseline wing. The lift force improvement at upstroke motion was higher than downstroke motion, whereas the drag increase was found to be less than the lift increase. The numerical simulation clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Meanwhile, there are no substantial dissimilarities between the baseline and WLE wings for AR 7.9 wing. A similar tendency was discovered in reference [21], where the WLE wing performed best during upstroke motion rather than downstroke action. The presence of WLE influences fluid flow properties where a twisted stream-wise vortical flow around the WLE was identified during both upstroke and downstroke motion, with the vortical flow being stronger during upstroke motion than downstroke motion.…”
Section: Results and Discussion Unsteady Analysis Of Rectangular Wingsupporting
confidence: 85%
See 1 more Smart Citation
“…Meanwhile, there are no substantial dissimilarities between the baseline and WLE wings for AR 7.9 wing. A similar tendency was discovered in reference [21], where the WLE wing performed best during upstroke motion rather than downstroke action. The presence of WLE influences fluid flow properties where a twisted stream-wise vortical flow around the WLE was identified during both upstroke and downstroke motion, with the vortical flow being stronger during upstroke motion than downstroke motion.…”
Section: Results and Discussion Unsteady Analysis Of Rectangular Wingsupporting
confidence: 85%
“…In contrast, no significant variations were noticed for the AR 7.9 wing. These results are identical to those reported in prior references [19,21], where the impact of WLE on a rectangular wing was explored and greater performance was seen during upstroke motion rather than downstroke motion. These findings imply that the effect of WLE on wing performance is strongly dependent on the AR and the wing motion.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, the WLE wing able to acquire the lift coefficient (Cl) after stall condition at angles α > 18°. WLE wing has superior forces after post-stall region compared to the baseline wing [18]. To analyze the WLE effect in various AR, L/D ratio has been carried out after stall condition i.e.…”
Section: Rectangular Wingmentioning
confidence: 99%
“…Miklosovic et al [18], conducted experimental trials on sinusoidal leading-edge wings, and their findings revealed that wings with larger amplitudes exhibited a more gradual stall pattern, attributed to stalls occurring later in the regions behind the peaks compared to those behind the troughs. Other scholars validated this through an experimental and numerical investigation of a rectangular wing incorporating the Wavy Leading Edge effect, demonstrating improved lift force during pitching motion with minimized stall [19][20][21], suggesting potential applications in wind turbines [22][23][24]. The experimental investigation performed by N. Karthikeyan et al [25,26] examined the impact of wavy leading edges, revealing tubercles' effectiveness in maintaining attached flow and reducing recirculating zones, although their influence on separation point variability and wake width post-stall requires further exploration.…”
Section: Introduction 1backgroundmentioning
confidence: 86%